Sistem Informasi Pendaftaran Member Baru pada Gym Cemerlang Berbasis Web dengan Metode Waterfall - Muhammad Izza Arya Dwipa; Cindy Taurusta; Yunianita Rahmawati; Rohman Dijaya (STIKOM Tunas Bangsa Pematangsiantar, 2026)
This study proposes a web-based information system for new member registration at Gym Cemerlang, developed to address the manual registration process that causes long queues, data recording errors, and inefficient membership data management. The system was developed using the Waterfall method, consisting of requirements identification, system design, implementation, testing, and maintenance. Data were collected through observation, interviews with the gym owner, and literature study. The system was built using ReactJS for the front-end, Express JS for the back-end, and PostgreSQL as the database, and was modeled using Use Case Diagrams and Data Flow Diagrams (DFD). The system involves two main actors: users (prospective members), who can view membership packages, register online, make payments, and check registration status; and administrators, who manage member data, membership packages, and registration confirmation through Create, Read, Update, and Delete (CRUD) operations. Functional testing was carried out using black-box testing, while user acceptance was planned to be measured using a Likert-scale questionnaire. The result of this research is a web-based registration system design that is expected to reduce queuing time, minimize recording errors, and provide real-time, self-service registration for prospective members, thereby improving the efficiency and quality of membership services at Gym Cemerlang.